Optimal and heuristic network coding algorithms for multi‐layered video broadcast - Bérczi‐Kovács, Erika R.; Király, Zoltán (Networks, 2018)
In this article we give network coding algorithms for multi‐layered video streaming. The problem is motivated by video broadcasting in a communication network to users with varying demands. We give a polynomial time algorithm for deciding feasibility for the case of two layers, and show that the problem becomes NP‐hard if the task is to maximize the number of satisfied demands. For the case of three layers we also show NP‐hardness of the problem. Finally, we propose a heuristic for three layers and give experimental comparison with previous approaches. © 2017 Wiley Periodicals, Inc. NETWORKS, Vol. 71(1), 51–59 2018